Self-assessment of primary school teachers’ competences in different areas: the influence of initial education and professional development - Bojana M. Marić; Radmila M. Rajinović; Milica V. Vojvodić Savić (Inovacije u Nastavi, 2025)
The paper analyses the self-assessment of primary school teachers’ competences in educational areas (natural sciences, social sciences, arts, and sports) by using the following dimensions: Learning Environment and Effective Communication, Assessment of One’s Own Work, Strategies and Lesson Planning, and Knowledge of the School Subject. The research was conducted on a sample of 180 primary school teachers from Serbia and a modified SITE II was used as the research instrument. The results show statistically significant differences between the self-assessments of the educational areas in relation to the dimensions of the Self-Evaluation of One’s Own Work and the Knowledge of the School Subject, which are reflected in the lower values in the areas of arts and sports. Initial education significantly influences the perception of the competences in two dimensions: Learning Environment and Effective Communication and Subject Knowledge in the field of natural sciences. Regarding professional development and self-assessment of achievements, it was proven that there is a statistically significant difference in the dimension of Knowledge of the School Subject in the field of arts and sports: respondents who have more professional development in the fields of social or natural sciences achieve lower results than those who have professional development in the field of sports and arts. The paper contributes to the understanding of the relationship between professional development and primary school teachers’ perceptions of competences, with implications for improving educational practices.